PROFESIONALISME, PENGALAMAN KERJA DAN PENDIDIKAN AUDITOR DI KANTOR AKUNTAN PUBLIK XYZ - Megawati .; Posma Sariguna Johnson Kennedy (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
The purpose of this study is to determine the level of professional, work experience and education that can affect the trust of clients to the services provided. In a professional the author of the value is from the professional judgment of the auditor's image or to the subject. Education and training should go hand in hand to obtain good service quality, in addition to general education that auditors should take the training should also be followed by auditors for professional development and knowledge development. The method of research that the authors use in this study is the analysis and comparison between the rules of Professional Standards of Certified Public Accountants and the real cases that the authors observe. Because auditor professionalism is managed in the Professional Standards of Certified Public Accountants and is contained in the regulations of the Indonesian Institute of Accountants. There is no significant difference between regulation and professional implementation.Keywords : professional, work experience and education.